Parental determinants associated with early growth after the first year of life by race and ethnicity - Aguayo, Liliana; Chang, Cecilia; McCormack, Luke R.; Shalowitz, Madeleine U. (Frontiers in Pediatrics, 2023)
Objective To investigate maternal and parental factors associated with changes in children's body mass index percentile (BMI-P) from 12 to 24 months. Methods Data from a prospective cohort of racially and ethnically diverse mothers, fathers, and children (n = 245) were used. Changes in BMI-P from 12 to 24 months of age were examined using height and weight measurements collected at both times. Separate longitudinal mixed-effects models with maximum likelihood were introduced to examine the determinants introduced by mothers and determinants from both parents among all children, and by race and ethnicity. Results Models that examine maternal and parental factors showed that children's overall BMI-P decreased from 12 to 24 months [β = −4.85, 95% confidence interval (CI), −7.47 to −2.23]. Stratified tests showed that White children whose parents graduated high school or completed a 4-year college degree or higher had greater decreases in BMI-P than White children born to parents with less than high school education (β = −60.39, 95% CI, −115.05 to −5.72; β = −61.49, 95% CI, −122.44 to −0.53). Among Hispanic/Latinx children, mean BMI-P significantly decreased from 12 to 24 months (β = −7.12, 95% CI, −11.59 to −2.64). Mother's older age (β = 1.83, 95% CI, 0.29–3.36) and child female sex (β = 11.21, 95% CI, 1.61–20.82) were associated with gains in children's BMI-P, while father's older age was associated with decreases (β = −1.19, 95% CI, −2.30 to −0.08). Conclusions Parental determinants associated with children's early growth varied by children's sex and racial and ethnic background. Results highlight the importance of understanding racial and ethnicity-specific obesity risks and including fathers in research.